Exploring students’ conceptual understanding and cognitive processes in human anatomy learning in the Biology Education Program Universitas Negeri Medan - Rahmad H. Gultom; Aristo Hardinata; Dina Handayani; Shofia Lubis; Nanda Pratiwi (Universitas Negeri Yogyakarta, 2026)
Human anatomy learning in biology education often faces challenges, including difficulties with 3D spatial visualization, high cognitive load, and persistent misconceptions in topics such as the digestive, circulatory, and respiratory systems, which contribute to low conceptual understanding. Although previous studies have identified these learning difficulties, limited research has examined the relationship between students’ conceptual understanding and cognitive processes in anatomy learning, particularly in Biology Education programs in Indonesia. This preliminary study aims to analyze the conceptual understanding and cognitive processes of Biology Education students at Universitas Negeri Medan using an exploratory mixed-methods approach involving 60 students from semesters 4–6. Data were collected through a two-tier diagnostic test (reliability = 0.85), think-aloud protocols based on the revised Bloom’s Taxonomy, classroom observations, and semi-structured interviews, and analyzed using SPSS 26. The findings show that most students were in the moderate and low categories of conceptual understanding, with cognitive processes dominated by lower- to mid-level skills (remembering 22%, understanding 30%) and limited higher-order thinking skills (HOTS). Misconceptions were found, including viewing enzyme function only as a metabolic process. Observations and interviews also revealed students’ dependence on rote memorization and passive learning. These findings highlight the need for adaptive, AI-based, and visually interactive anatomy learning to foster deeper understanding and support curriculum innovation in biology education.